Analysis of Cayenne Pepper Fruit (Capsicum frutescens) in Inhibiting HMG-CoA Reductase Activity as a Treatment for Hypercholesterolemia - La Ode Muh. Albar; Tien; Amiruddin Eso (Universitas Airlangga, 2024)
Background: Hypercholesterolemia is a major cause of cardiovascular disease and its incidence continues to increase. Statins are a group of hypercholesterolemic therapies known to trigger various side effects; therefore, statin alternatives need to be investigated. The cayenne pepper (Capsicum frutescens) contains secondary metabolites that inhibit the activity of cholesterol-forming enzymes (HMG-CoA reductase). Objective: The aim of this study was to identify the ability of C. frutescens fruit to inhibit HMG-CoA reductase activity to prevent hypercholesterolemia. Methods: This was a true experimental study using a posttest-only control group design. The independent variables were n-hexane, methanol, and ethanol extracts of C. frutescens fruit, each with a concentration of 0.01%, with HMG-CoA reductase activity as the dependent variable. Enzymatic activity was measured enzymatically using spectrometry. Results: The mean values of % inhibition from n-hexane, methanol, and ethanol extracts of C. frutescens and pravastatin were 95.74%, 104.70%, 100.11%, and 99.27%, respectively. The average specific activities of n-hexane, methanol, and ethanol extracts of C. frutescens and pravastatin were 0.5765, 0.6029, 0.5513, and 0.5716 units/mgP, respectively. There was a significant difference between the sample groups in the inhibition of HMG-CoA reductase activity. HMG-CoA reductase inhibitory activity was highest in the methanol extract, followed by the n-hexane extracts. The activity of these extracts was higher than that of pravastatin alone. Conclusion: The methanol extract showed the best inhibitory activity. C. frutescens has been shown to have great potential in inhibiting the activity of the enzyme HMG-CoA reductase and preventing hypercholesterolemia.